2020
DOI: 10.1109/access.2020.3007711
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Support in Engineering Courses: A Case Study in Brazil and Spain

Abstract: This work has been possible with the support of the Erasmus+ Programme of the European Union in its Key Action 2 "Capacity-building in Higher Education". Project W-STEM "Building the future of Latin America: engaging women into STEM" (Reference number 598923-EPP-1-2018-1-ES-EPPKA2-CBHE-JP). The content of this publication does not reflect the official opinion of the European Union. Responsibility for the information and views expressed in the publication lies entirely with the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 39 publications
1
5
0
2
Order By: Relevance
“…9 and 10, students who consider important the relationship with professors and students are more motivated and report a lower probability of abandonment than students who do not consider it. These results match with the results of the studies in Spain about the perceived supports and barriers for engineering students [50]- [51]. In these works, the authors concluded that peers and family are the most important supports, while teaching staff and institutional support have lower rates.…”
Section: Resultssupporting
confidence: 88%
“…9 and 10, students who consider important the relationship with professors and students are more motivated and report a lower probability of abandonment than students who do not consider it. These results match with the results of the studies in Spain about the perceived supports and barriers for engineering students [50]- [51]. In these works, the authors concluded that peers and family are the most important supports, while teaching staff and institutional support have lower rates.…”
Section: Resultssupporting
confidence: 88%
“…[ García-Holgado et al 2020] estudaram o suporte oferecido às estudantes do sexo feminino na Espanha e no Brasil. Comparando os dois cenários, foi constatado que o Brasil apresenta números menores em relac ¸ão ao apoio de familiares e amigos durante o percurso da graduac ¸ão e, em ambos os países, há um baixo suporte para as mulheres por parte dos professores e instituic ¸ões de ensino.…”
Section: Mulheres Em Steamunclassified
“…Thus, the gender gap in STEM areas is a global problem and it is caused by different factors (Lent et al, 1994 ; Osborne et al, 2003 ). Different studies have been developed to investigate the influence of stereotypes on the decisions made concerning higher education studies (Cadaret et al, 2017 ; García-Holgado et al, 2019 , 2020a , b ; Makarova et al, 2019 ; Powell et al, 2012 ; Tomassini, 2021 ; Verdugo-Castro et al, 2019 ). The starting point is that different obstacles and barriers generate segregation in tertiary studies, knowing which ones can tackle them to reduce the gender gap.…”
Section: Introductionmentioning
confidence: 99%
“…According to García-Holgado et al ( 2020a , b ), the support received before starting the undergraduate course the support received before entering a STEM career is a determinant factor. The peers and family are the most important perceived supports, while teaching staff and institutional support have lower rates.…”
Section: Introductionmentioning
confidence: 99%